Model Kepemimpinan Keluarga Sebagai Institusi Pendidikan Islam - Hakim, Lukman Nol (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The aim of this research is to formulate a family leadership model as an Islamic educational institution. This research method uses a qualitative approach. The data collection techniques used are documentation studies and text studies in order to find information or data about family leadership as an Islamic educational institution. The data collected was analyzed using content analysis techniques and explained descriptively. The results of the research show that the family leadership model as an Islamic education institution for individuals will have an ideal Muslim personality (moral), so parents are expected to provide guidance and provide qudwah for family leadership as an Islamic education institution. Among them, namely; provide guidance on faith and morals, guidance on worship, community mental development and intellectual development.